Book Review: Richard Barrett, The Values-Driven Organization: Unleashing Human Potential for Performance and Profit. (January 2016) - Jha, Snigdh
Richard Barrett, The Values-Driven Organization: Unleashing Human Potential for Performance and Profit, 2014, New York: Routledge, Taylor & Francis Group, pp. 247, ₹ 871, ISBN 978-0-415-81503-1.